Red blood cell fatty acid patterns from 7 countries: focus on the Omega-3 index - Schuchardt, Jan Philipp; Cerrato, Marianna; Ceseri, Martina; DeFina, Laura F.; Delgado Gonzales de Kleber, Graciela; Gellert, Sandra; Hahn, Andreas; Howard, Barbara V.; Kadota, Aya; Kleber, Marcus E.; Latini, Roberto; März, Winfried; et al. (Prostaglandins, leukotrienes and essential fatty acids, 2022)
Red blood cell (RBC) fatty acid (FA) patterns are becoming recognized as long-term biomarkers of tissue FA composition, but different analytical methods have complicated inter-study and international comparisons. Here we report RBC FA data, with a focus on the Omega-3 Index (EPA + DHA in% of total FAs in RBC), from samples of seven countries (USA, Canada, Italy, Spain, Germany, South Korea, and Japan) including 167,347 individuals (93% of all samples were from the US). FA data were generated by a uniform methodology from a variety of interventional and observational studies and from clinical laboratories. The cohorts differed in size, demographics, health status, and year of collection. Only the Canadian cohort was a formal, representative population-based survey. The mean Omega-3 Index of each country was categorized as desirable (>8%), moderate (>6% to 8%), low (>4% to 6%), or very low (≤4%). Only cohorts from Alaska (treated separately from the US), South Korea and Japan showed a desirable Omega-3 Index. The Spanish cohort had a moderate Omega-3 Index, while cohorts from the US, Canada, Italy, and Germany were all classified as low. This study is limited by the use of cohorts of convenience and small sample sizes in some countries. Countries undertaking national health status studies should utilize a uniform method to measure Omega-3 FA levels.